Dampak Penggunaan Teknologi Dalam Buku Life Hack Karya June Perry - Dwi Purnomo, Taufiq; Sidiq Pramono, Muhammad; Dwi Kurniawan, Eva (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Technology continues to develop very rapidly and can change the way humans live and work. This research aims to explore the impact of technology on humans referring to the novel entitled Life Hack by June Perry. However, technological developments also raise concerns about the replacement of human roles by smarter machines, loss of privacy and personal control, excessive dependence on technology, and other negative impacts. This research uses a literature study method with a qualitative approach. The results show that technology has benefits in increasing productivity in various fields and is also able to improve living standards. However, technology also has the potential to invade privacy and take over human work. So, the right policy is needed so that the benefits are maximized while minimizing the risks that may arise.